Koncepcja interesu spółki jako kluczowej konstrukcji w procesie dokonywania oceny sposobu pełnienia funkcji przez zarząd spółki - Stefanicki, Robert (L'vìvs'kij nacìnal'nij unìversitet ìmenì Ìvana Franka, 2019)
The interest of the company is a key construction of significance difficult to overestimate in the structure of commercial companies law. It is an essential point of reference in the process of assessing the manner in which the rights and obligations of partners are exercised, as well as performing functions by members of management and supervisory bodies. Difficulties with its decoding in the judicature come from the fact that it is a conglomerate of elements stemming from positive law and equity rules. The company’s interest criteria cannot be considered in isolation from the objectives of the company, the principles of cooperation for its achievement, and the respect of the loyalty requirement for exercising the competences of the management board members and company partners. Compliance with the interest of the company is the basic directive for the managers entrusted with the tasks entrusted to them in accordance with the requirements of professional diligence and its judicial assessment.
Keywords: interes spółki; zarząd spółki; zasada lojalności; ryzyko gospodarcze